Cash Flow Volatility and Firm Investment Behaviour: Evidence from African Listed Firms - Vengesai, Edson; Kwenda, Farai (Journal of Economics and Behavioral Studies, 2018)
This study explored the association between cash flow variability and investment behaviour of African listed firms. The research employed a dynamic panel data model estimated with the difference and system Generalised Method of Moments estimation techniques on a panel of 815 listed African non-financial firms. The estimation techniques control for unobserved heterogeneity, endogeneity, autocorrelation, heteroscedasticity and dynamic panel bias. Two different measures of volatility were employed; the exponentially weighted moving average, a forward-looking measure that captures innovations in cash flow volatilities and the coefficient of variation that captures the mechanical effect of the possible relation between cash flow levels and volatility. The results obtained suggested that cash-flow volatility is associated with average lower investment in African firms. These findings show that not only cash flows are an important determinant of investment decisions, but the variability of the cash flows also has a significant bearing on the investment levels of African firms. Cash flow volatility has a significant negative impact on investment even for firms with higher cash flows and unconstrained firms. African firms should not only aim at achieving higher cash flows, but the stability of the cash flows is equally important to sustain solid investment levels.